Effect of incorporating arboreal vegetation to Cynodon nlemfuensis diets during in-vitro ruminal fermentation - Ávila-Serrano, Narciso Ysac; López-Garrido, Serafín Jacobo; Galicia-Jiménez, Mónica Marcela; González-Crespo, Guillermo de Jesús; Camacho-Escobar, Marco Antonio (REVISTA TERRA LATINOAMERICANA, 2020)
Gramineae do not meet the needs of ruminants in the tropics, and their marked seasonal production causes disadvantages in animal production; in addition, high fiber levels and low protein content result in a higher production of greenhouse gases (GHG). For this reason, this study intended to supplement the diet by adding different foliage levels of tropical trees with the objective of evaluating the effect of incorporating 15, 30, and 45% of Moringa oleifera, Leucaena leucocephala or Guazuma ulmifolia on a diet based on Cynodon nlemfuensis grass during ruminal fermentation in vitro. The methodology consisted of ten treatments with different inclusion percentages of three different trees; the chemical composition, in vitro ruminal fermentation, dry matter degradation (IVDMD), pH, volatile fatty acid concentration (VFAs), biogas production and emission of methane (CH4) and carbon dioxide (CO2) were determined. Data were analyzed through a completely randomized design. The chemical composition of the diets showed differences (P < 0.05) when tree foliage was added gradually to the diet; the IVDMD was different (P < 0.05); pH of the treatments showed no differences (P > 0.05); VFA concentration was different (P < 0.05), the diet with 45% of Moringa oleifera had the best VFA concentration; however, the total biogas production and CH4 and CO2 concentrations were lower (P < 0.05) in the diet with 45% Leucaena leucocephala. In conclusion, the addition of 45% of Leucaena leucochephala to the diet improved chemical composition without affecting the VFA concentration and producing less CH4 and CO2 (18 and 24%, respectively).